TO THE TOPIC ON THE CONTRIBUTION OF INTERNATIONAL ORGANIZATIONS TO THE PRESERVATION OF THE BIO-RESOURCES STOCKS OF THE CASPIAN SEA - R. T. Asanov; E. A. Barskova; V. N. Pal'tsev; S. V. Shipulin (Юг России: экология, развитие)
Aim. The purpose of the work was to assess the activity of international organizations and determine theirs contribution to the preservation and rational use of water biological resources of the Caspian Sea and their inhabitant in the period after 1991.Results. The work presents a high management level of the state of water-biological resources during the history of the fishery basin. The management level of stocks, carried out by one country, including protection measures and artificial reproduction, allows to quickly respond to the dangers till the end of the XX century. It is shown that the activity of many out-regional and (or) non-state international organizations, heightened during the last the last-day period, is limited to piece of information, comprised of data collection about basin and preparing of the base for the adoption of binding decisions in the international legal field , often there is in a negative context for the Russian Federation. It is noted the leading input of specialized state departments, institutes and organizations to the protection, reproduction, researching of water bio-resources and their inhabitant, the results of which were integrated in the frames of work of the Commission on water bio-resources of the Caspian Sea.Main conclusions. The abstract presents suggestions on activity of designated global institution taking into account the beginning of the Agreement on protection and rational use of water biological resources of the Caspian Sea. The article presents proposals for the activity of international organizations at the Caspian basin.